Religious Moderation and Local Tradition: A Case Study of Sedekah Desa in East Java, Indonesia - Faradila Ema Nur Azizah; Wildhan Ichza Maulana; Bakhruddin Fannani (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2025)
This study investigates how the Sedekah Desa ritual practiced in Kandangan Village, East Java, embodies key dimensions of religious moderation. Employing a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation of ritual activities. The findings reveal that the tradition promotes four central indicators of religious moderation: (1) tolerance (tasāmuh)—evident in the inclusive prayer practices involving different religious groups; (2) equality (musāwah)—reflected in the shared participation across all social strata during communal meals; (3) justice (iʿtidāl)—symbolized through the jolen procession representing the balance between devotion to God (ḥabl min Allāh) and social solidarity (ḥabl min al-nās); and (4) adaptability (taṭawwur wa ibtikār)—seen in the community’s creative integration of Islamic values with local cultural expressions. These findings suggest that the Sedekah Desa ritual functions as a dynamic socio-religious mechanism that fosters inclusivity, intergroup harmony, and cultural resilience in contemporary Indonesian society.